2021
DOI: 10.1515/jbcpp-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Strain specific response of mice to IMQ-induced psoriasis

Abstract: Objectives Psoriasis is an autoimmune, inflammatory disease that needs a reliable animal model. Imiquimod (IMQ)-induced psoriasis is a widely used preclinical tool for psoriasis research. However, this model is sensitive to the genetic variation of mice. The present study explores mice’s genetic background on disease stability and severity induced by IMQ. Methods Three distinct strains of mice (Balb/c, C57BL/6, and Swiss albi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Among the preclinical studies, eight were in vivo studies ( Jain et al, 2016 ; Jia and Fang, 2017 ; Mao et al, 2017 ; Sun et al, 2017 ; Qu, 2018 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ), and the treatment of imiquimod (IMQ)-induced psoriasis-like mice comprised oral ( Jia and Fang, 2017 ; Qu, 2018 ) and topical ( Jain et al, 2016 ; Mao et al, 2017 ; Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) CUR. Four studies ( Jain et al, 2016 ; Jia and Fang, 2017 ; Mao et al, 2017 ; Qu, 2018 ) used BALB/c mice, and four studies ( Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used C57BL mice. Two studies ( Jia and Fang, 2017 ; Qu, 2018 ) reported intervention with CUR gavage, and six studies ( Jain et al, 2016 ; Mao et al, 2017 ; Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used a topical intervention method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the preclinical studies, eight were in vivo studies ( Jain et al, 2016 ; Jia and Fang, 2017 ; Mao et al, 2017 ; Sun et al, 2017 ; Qu, 2018 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ), and the treatment of imiquimod (IMQ)-induced psoriasis-like mice comprised oral ( Jia and Fang, 2017 ; Qu, 2018 ) and topical ( Jain et al, 2016 ; Mao et al, 2017 ; Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) CUR. Four studies ( Jain et al, 2016 ; Jia and Fang, 2017 ; Mao et al, 2017 ; Qu, 2018 ) used BALB/c mice, and four studies ( Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used C57BL mice. Two studies ( Jia and Fang, 2017 ; Qu, 2018 ) reported intervention with CUR gavage, and six studies ( Jain et al, 2016 ; Mao et al, 2017 ; Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used a topical intervention method.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies ( Jain et al, 2016 ; Jia and Fang, 2017 ; Mao et al, 2017 ; Qu, 2018 ) used BALB/c mice, and four studies ( Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used C57BL mice. Two studies ( Jia and Fang, 2017 ; Qu, 2018 ) reported intervention with CUR gavage, and six studies ( Jain et al, 2016 ; Mao et al, 2017 ; Sun et al, 2017 ; Zhang et al, 2019 ; Jin et al, 2020 ; Badanthadka et al, 2021 ) used a topical intervention method. Topical CUR has been formulated into different dosage forms with improved penetration and efficacy, including tacrolimus and CUR co-loading ( Jain et al, 2016 ), CUR-loaded nanoparticles ( Sun et al, 2017 ), CUR-loaded nanoparticles incorporated in silk fibroin hydrogel ( Mao et al, 2017 ), and CUR-loaded hyaluronic acid-modified ethosomes ( Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mice were randomly assigned to three treatment groups, i.e., the control, IMQ, and therapy groups. To establish the IMQ-induced psoriasis-like model, mice were treated with a daily topical dose of 62.5 mg of IMQ-cream (5%; Mingxinlidi, Sichuan, China) on the back for seven consecutive days based on a previous study [47]. The negative control was treated with the same dose of Vaseline cream alone.…”
Section: Characterization Of Pri@exomentioning
confidence: 99%